GAYA KOMUNIKASI PIMPINAN DALAM MEMOTIVASI KARYAWAN PRODUCTION HOUSE ONE MEDIA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to determine the communication styles used by the leadership in increasing the motivation of employees in the Makassar One Media Production House and to determine the inhibiting factors for the motivation of employees motivation to work in the Makassar One Media Production House employees. The results showed that (1) the communication style used by the leadership of the Makassar One Media Production House in motivating employee work is the equalitarian style which has open communication, meaning that every member of the organization or company can express ideas or opinions in such an atmosphere, enabling every member of the organization or company reaches an agreement and mutual understanding (2) There are several factors that can hinder the work motivation of the Makassar One Media Production House employees, namely: a) high workload, this factor makes employees often tired and becomes unfocused on their work, b ) poor labor division management, employees have to fill vacant positions and volunteer for the company, c) abuse of working hours, sudden work calls can make employees confused about scheduling.